Photocatalysis enabling acceptorless dehydrogenation of diaryl hydrazines at room temperature - Sahoo, Manoj K.; Saravanakumar, Krishnasamy; Jaiswal, Garima; Balaraman, Ekambaram (ACS Catalysis, 2018)
Aromatic azo compounds are privileged structural motifs, and they exhibit a myriad of pharmaceutical as well as industrial applications. Here, we report a catalytic acceptorless dehydrogenation of diarylhydrazine derivatives to access a wide variety of aryl-azo compounds with the removal of molecular hydrogen as the sole byproduct. This distinctive reactivity has been achieved under dual catalytic conditions by merging the visible-light active [Ru(bpy)(3)](2+) as the photoredox catalyst and Co(dmgH)(2)(py)Cl as the proton-reduction catalyst. The reaction proceeds smoothly under very mild and benign conditions and operates at ambient temperature. This dual catalytic approach is highly compatible with many different functional groups and has a broad substrate scope. We have also demonstrated the reversible hydrogen storage and release phenomenon on hydrazobenzene/azobenzene couple to show the utility of these compounds as hydrogen storage materials. Further diversification of azobenzene was shown by a transition metal-catalyzed azo-group-directed ortho-C-H bond functionalization.
Keywords: acceptorless dehydrogenation; Azo benzene; dual catalysis; Hydrogen; photoredox catalysis